Legal reflections to the Project of Statutory Law of Communication - Franco Loor, Eduardo (Revista Universidad de Guayaquil, 2010)
In the present partner-political and economic circumstances of the country, there is a great debate on the possibility that the National Assembly makes possible the creation of the Statutory law of Communication, legal instrument that in its project has received an ample rejection of some social political actor and mass media from opposition to the national government. Let us create the neces- sity that firmly the country counts on a Communication Act truely democratic, elaborated and cons- tructed by all the social actors and who represents an expeditious instrument to regulate and to in- dicate the high objectives of the national media and the science of the social communication. As the project is conceived at the moment, with technical-legal errors and imprecisiones, it is important to improve it so that it is left to its agreement and attachment to the Constitution of Montecristi 2008 clear that commands to be created this Law. It seems to us, in fundamental, if the their errors are corrected, viable thing, every time it keeps harmony with the main international instruments that Ecuador is signatory and therefore it is had it jeopardize to respect and to accept.
Keywords: International constitution; Statutory law of Communication; Freedom of expression and opinion; biofuels; social profesionalización of journalists and signallers